2023
DOI: 10.1021/acsanm.3c04427
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed UV Photodiodes Based on Cs2Ag0.35Na0.65InCl6 Perovskite Nanocrystals

Xiaoyu Huang,
Hiroyuki Yamada,
Hong-Tao Sun
et al.

Abstract: Halide perovskites stand out as promising materials for the realization of high-performance photodetectors. However, the inherent instability and lead toxicity are still obstacles facing the wide practical application of photodetectors. In this work, the first highly responsive lead-free perovskite photodiode based on Cs 2 Ag 0.35 Na 0.65 InCl 6 nanocrystals (NCs) is demonstrated. The composition tuning strategy is introduced to enhance the device performance of photodiodes. Employed with a device structure co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…11,32,41 Cs 2 AgInCl 6 NCs are particularly advantageous for selfpowered UV photodetection on account of their intriguing optoelectronic properties and high optical absorption co-efficient in the UV region with high bandgap. 31,32,42 Furthermore, it is important to note that the development of an ecofriendly UV photodetector is still in a nascent stage.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,32,41 Cs 2 AgInCl 6 NCs are particularly advantageous for selfpowered UV photodetection on account of their intriguing optoelectronic properties and high optical absorption co-efficient in the UV region with high bandgap. 31,32,42 Furthermore, it is important to note that the development of an ecofriendly UV photodetector is still in a nascent stage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In metal halide lead-based perovskites, very few systems have shown UV detection with limited performance, which are not completely UV but also combined with visible light with broadband detection. , Stability and toxicity issues are still major problems with these materials that remain unaddressed. Here, lead-free halide double perovskite (LFHDPs) are a very good alternative material for developing self-powered UV photodetectors. ,, Cs 2 AgInCl 6 NCs are particularly advantageous for self-powered UV photodetection on account of their intriguing optoelectronic properties and high optical absorption coefficient in the UV region with high bandgap. ,, Furthermore, it is important to note that the development of an ecofriendly UV photodetector is still in a nascent stage.…”
Section: Introductionmentioning
confidence: 99%
“…Lead-free double perovskites, obtained by replacing two divalent lead ions of lead halide perovskite materials with one monovalent cation and one trivalent cation, are a rising star among photosensitive materials because not only do they have excellent perovskite optoelectronic properties, but they have been structurally tuned to be less toxic and more stable . Since Creutz et al and Locardi et al first reported the syntheses of Cs 2 AgBiCl 6 and Cs 2 AgInCl 6 double perovskite nanocrystals, , numerous lead-free double perovskites nanocrystals have been successfully obtained and applied to solar cell devices, photocatalytic reactions, UV and X-ray detectors, and light emitting diodes (LEDs) . Furthermore, recent reports have demonstrated that photosensitive materials in combination with graphene nanosheets with excellent charge transport capabilities could prominently improve the charge separation and transfer. However, to the best of our knowledge, in situ grown composites of Cs 2 AgInCl 6 nanocrystals supported by graphene and application of such composites in PEC biosensing have not yet been reported; in particular, the combination with intriguing sensing mechanisms is expected to improve the photoelectric performance, which provides a unique perspective to build a utility and efficient PEC sensing strategy with simple operation and low expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, self-powered photodiodes do not require an external voltage source and can detect light with low power consumption. 5–7 Most commercially available infrared detectors rely on epitaxially grown III–V and HgCdTe-based photodetectors, which require complex growth processes such as molecular beam epitaxy (MBE) and metal–organic chemical vapor deposition (MOCVD), resulting in high production costs and many manufacturing steps. 8 Therefore, there is an urgent need to develop optical absorbers to easily fabricate SWIR photodetectors and improve device performance.…”
Section: Introductionmentioning
confidence: 99%